Adoption of Spices Cultivation Technology by the Growers in Shibganj Upazila under Bogura District of Bangladesh (The Agriculturists, 2020)
Traditionally, spices are important components used for preparation of everyday menu, especially for Bangladeshi. In this connection, Spices Research Center under Bangladesh Agricultural Research Institute (BARI) has been releasing new spices varieties but there is dearth of research on the adoption of these newly released spices varieties. Therefore, the present study aimed at to examine the extent of adoption of spices cultivation technology by the growers in Shibganjupazila under Bogura district. Data were collected from 90 household heads selected following proportionate random using a structured interview schedule. Major cultivating spices varieties which are noticed in the study area are BARI piaz1, BARI ada2, BARI holud5. Under the three major spices variety, 43.3 percent area was covered by small scale spices cultivation, 42.2 percent by medium scale and 14.5 percent was covered by large scale area of spices cultivation. Findings revealed that huge majority (80.0%) of the respondents had medium adoption of BARI piaz1 whereas almost all (93.3%) of them had medium adoption of BARI ada2. On the other hand, more than half (53.3%) of the respondents had low adoption of BARI holud5 whereas 40.0 percent of them had medium and 6.7 percent had high adoption of the same. Vital perceived benefits that attracted the respondents in spices cultivation were higher price, yield and quality of the technologies than those of previous. BARI holud5 was found more profitable (BCR 1.7) than BARI piaz1 (BCR 1.3) and BARI ada2 (BCR 1.3). Respondent farmers’ education, farm size, innovativeness, extension contact, knowledge on spices cultivation and annual family income showed significant and positive relationship with their adoption of spices technology.The Agriculturists 2020; 18(1) 81-93